PENINGKATAN MUTU PENDIDIKAN MELALUI PELATIHAN PEMBELAJARAN MENDALAM BAGI GURU SMA DI SULAWESI SELATAN - Alwi, Alimin; Achmad, Asmar; Asrianingsih (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2025)
This community service program aims to improve the quality of education through in-depth learning training for teachers in South Sulawesi. The program is implemented by the South Sulawesi Teacher Training Center in collaboration with universities, with the main target being teachers at various levels of education. The methods used to carry out the activities include interactive lectures, group discussions, learning simulations, and assistance in developing collaborative inquiry-based learning plans. The training material focused on strengthening growth mindset, deep learning frameworks, learning planning and implementation, assessment, and reflection on pedagogical practices. The results of the activity showed an increase in teachers' understanding and skills in designing and implementing meaningful, conscious, and enjoyable learning. In addition, teachers are better able to holistically integrate aspects of thinking, feeling, tasting, and exercising in the teaching and learning process. Thus, this training contributes to improving teacher professionalism and is one of the effective strategies in efforts to improve the quality of education in South Sulawesi.